DIKOTOMI PENEGAKAN HUKUM PELANGGARAN LALULINTAS TERHADAP PENGENDARA YANG TIDAK MENGGUNAKAN HELM DI KOTA KENDARI - Wa Ode Adriani Sukma; Sabrina Hidayat; Kamaruddin (Halu Oleo University, 2024)
This research is based on the phenomenon of the people of Kendari City who think that riding on the road using a motorbike does not require wearing a helmet, especially at certain moments. This momentum such as the delivery of a corpse or even to the celebration of a democratic party, like a campaign in public areas. Some people of Kendari City only wear hats and peci (songko) at certain seasons, and some choose not to wear any head protection at all. Due to societal realities, the purpose of this research is to ascertain how law enforcement responds to drivers who don’t wear helmets in accordance with sociocultural circumstances and to understand Kendari City’s traffic law system from the perspective of Lawrence M. Friedman’s theory. The research method used is a normative-empirical method. The research results findings demonstrate that when law enforcement personnel’s roles are in conflict with the sociocultural context of Kendari City society, the application of Article 291 of the Traffic Law fails to work as best it might. At some times, including during campaigns or when delivering corpses, law enforcement officials in the traffic sector appear to find it difficult or impossible to enforce the law against drivers who don’t wear helmets. Therefore, the situation indicates that Article 291 of the Traffic Law’s traffic system doesn’t work as expected.